Comparative study of laser versus open lateral internal sphincterotomy in the treatment of anal fissure - Rajkumar Verma; Pooja Prajapati; Prashant Kumar (Asian Journal of Medical Sciences, 2023)
Background: Anal fissure is a common proctological problem that causes anal pain during and after defecation. An anal fissure is a linear ulcer that presents at the anal verge. It is more common in females than males and can be seen either in the anterior or posterior midline, just distal to the dentate line. Aims and Objectives: Comparison of Laser versus Open lateral internal sphincterotomy (LIS) in the treatment of anal fissures. Materials and Methods: The study was conducted in 50 cases of Open LIS compared with 50 cases of laser LIS (LLIS) in patients admitted to the Department of Surgery, M.L.B. Medical College, Jhansi (UP), India, between January 2021 and June 2022. Results: Out of 50 cases of open LIS, 10 patients presented with bleeding, 10 patients presented with hematoma/perianal swelling and 5 patients presented with pain as compared to 50 cases of LLIS, hematoma/perianal swelling (1 patient) and pain (2 patients) were found as an early post-operative complication. Mean hospital stay was 2.84±1.128 days in Open LIS as compared to 1.02±0.141 days in LLIS. The pain was presented in 1 patient as the only late post-operative complication in LLIS as compared to pain (25 patients), bleeding (10 patients), infection (2 patients), and flatus incontinence (1 patient) in Open LIS, at 2 weeks follow-up and recurrence in 1 patient in laser and in 3 patients in open LIS at 6 weeks follow up. Conclusion: LLIS significantly reduces early postoperative complications such as postoperative pain, bleeding, and hematoma as compared to open LIS. The duration of hospital stay was significantly less in LLIS in comparison to open LIS. None of the patients presented with the flatus or stool incontinence who had undergone LLIS while in Open LIS, 12% of patients presented with flatus incontinence, and 2% of patients presented with stool incontinence during follow-up in 2–6 weeks.